Development of Practical Guidance based on Research to Improve Science Process Skills and Learning Outcome in Biology Education Students - Karunia Galih Permadani; Ika Sukmawati (Indonesian Journal of Biology Education, 2021)
Efforts to improve students' understanding of science process skills in learning the Animal Development Structure subject are developing a research-based Practicum Manual for the Animal Development Structure course. The purpose of this research is to develop a research-based Practicum Manual for Animal Development Structure courses that are suitable for use as a learning resource and experiment in the Animal Development Structure course. The development of laboratory engineering modules uses the ADDIE development model (Analyze, Design, Development, Implementation, Evaluation). This research is a development research and uses questionnaire and test instruments. The data were analyzed descriptively qualitatively and the results were analyzed using the Gain normality test. Experts in developing teaching materials and materials assess that the lecture modules developed are of good qualifications and are suitable for use. The trial results on a limited scale as well as the lecture module field tests are in good qualifications.